Aplikasi Sistem Pakar Untuk Diagnosa Penyakit Diabetes Melitus dengan Algoritma Certainty Factor Berbasis Web - Rizka Nurliana Putri; Leonard Goeirmanto (JURNAL APLIKASI DAN INOVASI IPTEKS "SOLIDITAS" (J-SOLID), 2020)
Information technology is currently very rapidly developing. information technology can be used in all aspects, including for the world of health. currently an expert system application has been developed by researchers with a variety of methods. The expert system itself is a system that adopts the way of thinking of an expert into a computer system. expert systems for diagnosing a disease make it easy for people to consult about their health and illness without having to meet directly with an expert or doctor. the results of the expert system diagnosis can be used as a reference if you want to consult a doctor when conducting a health test. The method used in the system is certainty factor. Certainty factor is an algorithm used when facing a problem for which the answer is uncertain. This uncertainty can be a probability. Certainty Factor states confidence in an event (or facts or hypotheses) based on expert evidence or judgment. application of an expert system with this certainty factor method successfully diagnoses well according to the weight value given by the expert or doctor. This expert system will also be very useful for the community as an educational medium so that people are more aware of diabetes, the symptoms of diabetes and solutions that must be done from diabetes.